DYSTOCIA DUE TO FETAL ARTHROGRYPOSIS IN A SHEEP - ANUSHA, K; NAIDU, G VENKATA (The Indian Journal of Animal Reproduction, 2015)
A case of dystocia in a sheep due to fetal arthrogryposis and its successful clinical management is discussed.
Keywords: Dystocia; Arthrogryposis; Sheep